Implementasi Pembelajaran Tahfidz Interaktif dalam Meningkatkan Motivasi dan Karakter Siswa di SDIT Az-Zahra Islamic School - Dimas Tri Is Koerniansyah; Ellisa Fitri Tanjung (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This community service activity aims to implement an interactive Tahfidz learning model to enhance students’ motivation and Qur’anic character at SDIT Az-Zahra Islamic School. The program was carried out for ten days and consisted of three main stages: observation and mapping of students’ memorization ability, implementation of interactive Tahfidz through small-group murojaah and memorization games, and evaluation through reflection and feedback. The method used was participatory, emphasizing student involvement, collaboration, and reward-based learning. The findings indicate that interactive Tahfidz learning increases students’ motivation, confidence, and discipline in memorizing the Qur’an. Furthermore, students showed improved Qur’anic character, including honesty, cooperation, and responsibility. This approach provides an enjoyable and meaningful learning experience that encourages spiritual growth and strengthens students’ attachment to the Qur’an. The implication of this program highlights that integrating interactive methods into Qur’anic education can effectively support moral and spiritual development in elementary-level students.